Pirolisis Limbah Pelepah Sawit Menjadi Bio Oil Menggunakan Ni.Mo/Lempung Cengar - Adelina Samosir; Syaiful Bahri; Aman Aman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Fuel is a very important energy. The increase need fuel and diminishing avaibility of fossil fuel. It is also increasing awareness to find alternative energy technology. one of thesealternatives energy is bio-oil. bio-oil is a fuel, organic liquid produced by pyrolysis process. Pyrolysis of biomass a palm midrib. in a palm tree produces 40-50 midrib/tree/year so thatone hectare of palm can produce 6400 to 7500 midrib/year. manufacture of bio-oil with pyrolysis process can be done using Ni-Mo catalyst/Clay. This study aims to find the performance of the catalyst Ni-Mo/Clay Cengar (0%, 1%, 3% and 5% w / w biomass) against yeild bio-oil produced and characterize physical and chemical properties. pyrolysis palm midrib -40+60 mesh size of 50 grams, 0.5 grams of catalyst in 500 ml silinap performed at a temperature of 330 oC. The development Ni-Mo metal on clay cengar shown to affect the yield bio-oil is obtained, while the results obtained yield at 0%, 1%, 3% and 5%, respectively, 49.40%, 58.87%, 53.11% and 49.92%. bio-oil yield results that the maximum 58.87% obtained on treatment using a metal carrier Ni-Mo/clay cengar 1%. characterizationbiooil physical properties of of Ni-Mo/clay impurity 1% w/w has physical characteristics that density 0.9466 g/ml, 10.87 cSt viscosity, flash point 55C, and acid number 0.0751 g NaOH /g sample. based on the results of the analysis of the chemical components bio-oil is best obtained in the treatment bio-oil Ni-Mo/clay impurity 3% w/w bio-oil contains alcohol 7.35%, 0.35% phenol and other compounds 6.72% hydrocracking.Keyword : Bio-oil, a palm midrib, Pyrolysis, Ni.Mo/Clay Cengar